The Process of Steel Manufacturing: Techniques, Technologies, and Environmental Impacts - Xaminov Burkhon Turgunovich; Bakhriddinova Dilnora Sharifjon kizi; Khusanova Sarvinoz Alisher kizi; Mirzayev Islambek Umarali ugli (Global Scientific Publishing, 2023)
Steel manufacturing is among the world's largest industries, with millions of tons of steel produced every year. This study aimed to analyze the steel manufacturing process, discuss the technological techniques utilized, evaluate the environmental impact of this industry, and assess the current state of steel manufacturing in Uzbekistan.
Keywords: Steel Manufacturing; Techniques; Technologies